2019
DOI: 10.1145/3341685
|View full text |Cite
|
Sign up to set email alerts
|

Fairness in responsive parallelism

Abstract: Research on parallel computing has historically revolved around compute-intensive applications drawn from traditional areas such as high-performance computing. With the growing availability and usage of multicore chips, applications of parallel computing now include interactive parallel applications that mix compute-intensive tasks with interaction, e.g., with the user or more generally with the external world. Recent theoretical work on responsive parallelism presents abstract cost models and type systems for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…In contrast, Muller et al [24] design and prove responsiveness for a probabilistic scheduler of cooperative threads with priorities. The work is based on the cooperative suspension of threads but they interrupt threads that do not suspend; this prevents assumptions on the finiteness of local computation but compromises the guarantees of cooperative scheduling.…”
Section: :24mentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, Muller et al [24] design and prove responsiveness for a probabilistic scheduler of cooperative threads with priorities. The work is based on the cooperative suspension of threads but they interrupt threads that do not suspend; this prevents assumptions on the finiteness of local computation but compromises the guarantees of cooperative scheduling.…”
Section: :24mentioning
confidence: 98%
“…In rules (19) and (20) we must reset the counter to c ′ = 0. Finally, for (21), (24), and (23) the value of the counter does not matter, we arbitrarily choose c ′ = c.…”
Section: :32mentioning
confidence: 99%
“…This research have shown that this bound is not purely theoretical and can in fact be realized efficiently in practice [1-3, 7, 12, 14, 16, 21, 23, 35], usually by using a variant of work stealing. Recent work has also made some progress extending this scheduling theory to account for latency [31] and competition among tasks, by allowing tasks to declare priorities [34,43].…”
Section: Related Workmentioning
confidence: 99%
“…Henry [28] gave a fair scheduler for processes on UNIX systems. Muller, Acar, and Harper [49] and Muller, Westrick, and Acar [50] studied fair scheduling for interactive computation and in the presence of priorities. Lahav et al [39] gave an account of process fairness under weak memory models.…”
Section: Fairnessmentioning
confidence: 99%